Low density steel 1·2C–1·5Cr–5Al designed for bearings. (September 2014) - Yi, H. L.; Cai, H. L.; Hou, Z. Y.; Pang, J. C.; Wu, D.; Wang, G. D.
<x content-type="archive" xml:space="preserve">Abstract</x> A novel alloy design, designated as 1·2C–1·5Cr–5Al, has been proposed with high aluminium(∼5 wt-%) and more carbon(∼1·2 wt-%) addition into the classical 1C–1·5Cr bearing steel for lowering density and improving performance simultaneously, which is approximate 8 wt-% lighter than convention. In order to understand preliminarily the suitability of the novel alloy for bearing application, the martensite starting temperature and hardness, related to microstructure evolution and mechanical properties, respectively, after partial austenitisation treatment with undissolved carbides have been investigated carefully. The martensite starting temperature is comparable with conventional 1C–1·5Cr alloy. The hardness of 860±3 HV20 achieved is much higher than convention.